Spy pilot : Francis Gary Powers, the U-2 incident, and a controversial Cold War legacy /: Francis Gary Powers, the U-2 incident, and a controversial Cold War legacy. (2019) - Jr, Powers, Francis Gary, 1965-; Dunnavant, Keith
No abstract available